2013
DOI: 10.1007/s12640-013-9430-3
|View full text |Cite
|
Sign up to set email alerts
|

The Predominant Protective Effect of Tianeptine Over Other Antidepressants in Models of Neuronal Apoptosis: The Effect Blocked by Inhibitors of MAPK/ERK1/2 and PI3-K/Akt Pathways

Abstract: Tianeptine (Tian) possesses neuroprotective potential, however, little is known about the effect of this drug in models of neuronal apoptosis. In the present study, we aimed (1) to compare the neuroprotective capacities of some antidepressants (ADs) in the models of staurosporine (St)- and doxorubicin (Dox)-evoked cell death, activating the intracellular and the extracellular apoptotic pathway, respectively; (2) to identify the Tian-modulated steps underlying its neuroprotective action; (3) to test the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 70 publications
3
18
1
Order By: Relevance
“…Caspase-3 activity was measured with a fluorometric method employing the fluorogenic substrate, AC-DEVD-AMC as described previously (Jantas et al, 2014a). The UN-and RA-SH-SY5Y cells were treated with mGluR II/III activators and St or Dox for 6 and 12 h, respectively.…”
Section: Assessment Of Caspase-3 Activitymentioning
confidence: 99%
“…Caspase-3 activity was measured with a fluorometric method employing the fluorogenic substrate, AC-DEVD-AMC as described previously (Jantas et al, 2014a). The UN-and RA-SH-SY5Y cells were treated with mGluR II/III activators and St or Dox for 6 and 12 h, respectively.…”
Section: Assessment Of Caspase-3 Activitymentioning
confidence: 99%
“…Antidepressants used were SSRIs (fluoxetine and paroxetine), NRIs (reboxetine), TCAs (imipramine, amitriptyline and DMI) and monoamine oxidase inhibitors (MAOIs, l-deprenyl and pargyline). As mentioned in materials and methods, the selection of these antidepressant concentrations are based on the published papers (Lai & Yu 1997, Koshimura et al 2000, Seymour et al 2003, Taler et al 2007, Hisaoka et al 2008, Fisar et al 2010, Leskiewicz et al 2013, Jantas et al 2014), in which different antidepressants in clinically relevant concentrations exhibited neuronal protection without effects on cell viability when used alone in SH-SY5Y cells or PC12 cells. Based on the provided information, we performed preliminary experiments and selected two concentrations for each antidepressant under the present experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the neuroprotective effects accounted by antidepressants, as demonstrated in the present study, may act via these pathways too. It was reported that the antidepressants tianeptine and moclobemide, both MAOIs, prevented apoptosis caused by toxic agent staurosporine, doxorubicin or FasL in vitro through motivating of the ERK1/2 (Chiou et al 2006, Jantas et al 2014). Likewise, imipramine, amitriptyline, DMI, citalopram, fluoxetine, reboxetine and tianeptine blocked dexamethasone-induced decreases in cell viability and proliferation rate trough activating of ERK1/2 (Leskiewicz et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations